Two Band Model for Diluted Magnetic Semiconductors: Study of the Ferromagnetic Transition Temperature - Thai, Vu Kim; Tuan, Hoang Anh (Communications in Physics, 2011)
The ferromagnetic transition temperature (Tc) of a two band model for diluted magnetic semiconductors (DMS) is calculated by using the coherent potential approximation (CPA). It is shown that Tc is strongly parameter dependent on density of the carriers, magnetic coupling constants, and the hopping terms. The maximal Tc of the two band model is found when both impurity bands fully overlap and this value is approximately twice larger than the highest Tc obtained in the single band model.